2015
DOI: 10.1590/1519-6984.00413suppl
|View full text |Cite
|
Sign up to set email alerts
|

Influence of urban area on the water quality of the Campo River basin, Paraná State, Brazil

Abstract: The Campo River basin is located on the third plateau of the Paraná State or trap plateau of Paraná, at the middle portion between the rivers Ivaí and Piquiri, southern Brazil, between the coordinates 23° 53 and 24° 10' South Latitude and 52° 15' and 52° 31' West Longitude. The basin has 384 Km² area, being 247 km 2 in the municipality of Campo Mourão and 137 km 2 in the municipality of Peabiru, in Paraná State. The Campo River is a left bank tributary of the Mourão River, which flows into the Ivaí River. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 12 publications
2
7
0
11
Order By: Relevance
“…Although the TC and TTC indexes were variable during the year, there were no significant relationships with the rainfall and temperature. The data obtained in this study in the city of Cascavel suggest anthropogenic interference with water quality, probably caused by the disposal of domestic sewage (Rodriguez-Mozaz et al, 2015); the presence of coliforms in all samples was also reported by Carvalho et al (2015) for the Campo River basin.…”
Section: Discussionsupporting
confidence: 65%
“…Although the TC and TTC indexes were variable during the year, there were no significant relationships with the rainfall and temperature. The data obtained in this study in the city of Cascavel suggest anthropogenic interference with water quality, probably caused by the disposal of domestic sewage (Rodriguez-Mozaz et al, 2015); the presence of coliforms in all samples was also reported by Carvalho et al (2015) for the Campo River basin.…”
Section: Discussionsupporting
confidence: 65%
“…Figura 4: Frequência (%) de projetos de iniciação científica relacionados a "Água", desenvolvidos em uma IES privada entre os anos de 2004 e 2018, de acordo com os cursos de graduação. organismos aquáticos e à saúde humana que a mesma pode provocar (CARVALHO et al, 2015). A água, fonte de vida e recurso limitado, vem sendo degradada em decorrência do aumento populacional e da poluição ambiental afetando milhares de pessoas no mundo, as quais apresentam algum tipo de enfermidade em função de sua baixa qualidade (MENDES et al, 2007).…”
Section: Resultados E Discussõesunclassified
“…The presence of phosphorus in watersheds during the rainy season is indicative of the entry of fertilizers, sewage and industrial due to runoff (Bortoletto et al, 2015;Carvalho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%